Referência invisibilizada Maria Odília Teiceira, Leodegária de Jesus e Adélia Sampaio - Fabiana Santos Souza; Hellen Stephanye Rosa de Oliveira; Josileide Veras de Sousa (Les Cahiers ALHIM)
This article consists of biographies of black women from three different areas of activity, namely Maria Odília Teixeira, Leodegária de Jesus and Adélia Sampaio. Women who are pioneers in their respective areas and that have suffered the process of epistemic racism, despite its numerous contributions, racist strategy of invisibilize and neglect knowledge produced by black people. We aim to collaborate so that the plurality of knowledge and epistemologies are recognized. Thus enabling the construction of new worlds, new perspectives of knowledge and the most urgent, which is the coexistence of specialists in various subjects, being black women along with black men, white women and white men.